Genetic differentiation in the nearly extinct harlequin frogs (Bufonidae: Atelopus), with emphasis on the Andean Atelopus ignescens and A. bomolochos species complexes - Guayasamin, Juan M.; Bonaccorso, Elisa; Duellman, William E.; Coloma, Luis A. (Zootaxa, 2010)
The evolutionary relationships of Andean harlequin frogs were studied, with emphasis on the Atelopus ignescens and A. bomolochos species complexes. Sampling included 53 individuals belonging to eight taxa and several unidentified species, for which a mitochondrial fragment (16S, tRNA-Leu, ND1, and tRNA-Ile; 1294 bp) was amplified. Bayesian and Maximum Likelihood analyses were used to obtain hypotheses of relationships. The resulting phylogeny indicates that the species complexes are non-monophyletic. Additionally, analyses support the presence of four or five undescribed species. Most of these populations and newly discovered lineages have not been recorded in several years and are presumed extinct, the exception being two populations of probably new taxa from mid-elevations in southeastern Ecuador found during recent field surveys. Although sampling is limited, geographic isolation is the most plausible cause of differentiation among populations and taxa.